Mineralogy and petrography of C asteroid regolith: The Sutter's Mill CM meteorite. (November 2014) - Zolensky, Michael; Mikouchi, Takashi; Fries, Marc; Bodnar, Robert; Jenniskens, Peter; Yin, Qing‐zhu; Hagiya, Kenji; Ohsumi, Kazumasa; Komatsu, Mutsumi; Colbert, Matthew; Hanna, Romy; Maisano, Jessie; et al.
Abstract Based upon our characterization of three separate stones by electron and X‐ray beam analyses, computed X‐ray microtomography, Raman microspectrometry, and visible‐IR spectrometry, Sutter's Mill is a unique regolith breccia consisting mainly of various CM lithologies. Most samples resemble existing available CM2 chondrites, consisting of chondrules and calcium‐aluminum‐rich inclusion (CAI) set within phyllosilicate‐dominated matrix (mainly serpentine), pyrrhotite, pentlandite, tochilinite, and variable amounts of Ca‐Mg‐Fe carbonates. Some lithologies have witnessed sufficient thermal metamorphism to transform phyllosilicates into fine‐grained olivine, tochilinite into troilite, and destroy carbonates. One finely comminuted lithology contains xenolithic materials (enstatite, Fe‐Cr phosphides) suggesting impact of a reduced asteroid (E or M class) onto the main Sutter's Mill parent asteroid, which was probably a C class asteroid. One can use Sutter's Mill to help predict what will be found on the surfaces of C class asteroids such as Ceres and the target asteroids of the OSIRIS‐REx and Hayabusa 2 sample return missions (which will visit predominantly primitive asteroids). C class asteroid regolith may well contain a mixture of hydrated and thermally dehydrated indigenous materials as well as a significant admixture of exogenous material would be essential to the successful interpretation of mineralogical and bulk compositional data.